Life cycle analysis on the design of induction motors. - Torrent, Marcel
Purpose Herein is reported an application of life cycle analysis (LCA), using the Methodology for the Ecode-sign of Energy Using Products (MEEUP), in order to assess the influence of some design parameters in the environmental impact of three phase induction motors. A motor design procedure to minimize the total environmental impact, based on data obtained from commercial motors, is presented. This procedure is specially intended for the low power range due to the greater potential for energy savings in motors having an output power of 0.75 to 4 kW. Methods A procedure has been developed, based on previously acquired dta, to determine the parameters required for application of the MEEUP methodology. These comprise the quantity of each of the motor's main constituent materials used in the production phase, and the two operating variables that directly influence the LCA results : output powr and efficiency. Results and discussion. The procedure was applied to two 1.5 kW induction motors of different efficiency (according to standard IEC60034-2-1). The calculation results were compared satisfactorily with the laboratory test results. The total environment impact of the two real motors and of the proposed motor was determined in the production, service life and end of life phases. Conclusions. Given the potential for energy savings in electric motors, LCA-based environmental impact assessment should be incorporated into motor design.
Keywords: Efficiency; Environmental impact; Induction motor; Life cycle; Losses